Toko Jamu “Kwat Shae” Untuk Menyuarakan Isu Street Harassment Catcalling - Wattimena, Louisiana; Murwanti, Aprina (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2023)
Catcalling is a verbal sexual harassment that is a fraction of an underestimated street harassment but have a huge impact towards its victim, which is women at any age. The root of this problem is the normalization of catcalling by society that leads to bigger problems among civilization. Herbal Shop is one of the solutions for people to gain access to traditional medicine. People’s understanding in herbal medicine efficacy is an interesting approach to deliver a sensitive issue; where in this case, catcalling. By using a parody of a herbal shop analogy, issue of catcalling could be wrapped into a familiar and a lighter form to deliver. Installation of “Kwat Shae” herbal shop as an introduction of street harassment issue of “catcalling” appropriates a herbal shop installation that evoke false way of thinking from society about catcalling that “heals” people’s perception just like herbal medicine.